2020
DOI: 10.1002/batt.201900204
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic‐Based Solid‐State Supercapacitors: Enabling Redox Reaction by In Situ Electrochemical Treatment

Abstract: The quest for supercapacitors that can hold both high energy and power density is of increasing significance as the need for green and reliable energy storage devices grows, for both large-scale and integrated systems. While supercapacitors for integrated technologies require a solid-state approach, gel-based electrolytes are generally not as efficient as their aqueous counterparts. Here we demonstrate a strategy to enhance the performance of quasi-solid-state supercapacitors made by graphitized silicon carbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…This suggests that the formation of the additional C-OH bond occurs mainly at the edges or grain boundaries of the graphene, rather than the basal plane, due to the higher surface energy of the defective grain boundaries promoting the formation of functional groups [47]. Interestingly, a similar surface functionalization phenomenon was observed in our recent study, where water splitting was purposely induced in-situ in a supercapacitor cell with graphene electrodes and acidic electrolyte (sulfuric acid and poly vinyl alcohol) [43]. This functionalization, promoted by the availability of free protons and hydroxyl groups in the electrolyte, led to an increased amount of C-OH and COOH functionalization on the graphene, which in turn, among others, greatly improved the wettability of the electrodes to the electrolyte and led to a marked enhancement of the double-layer capacitance.…”
Section: Surface Conditioning Mechanismsupporting
confidence: 76%
See 1 more Smart Citation
“…This suggests that the formation of the additional C-OH bond occurs mainly at the edges or grain boundaries of the graphene, rather than the basal plane, due to the higher surface energy of the defective grain boundaries promoting the formation of functional groups [47]. Interestingly, a similar surface functionalization phenomenon was observed in our recent study, where water splitting was purposely induced in-situ in a supercapacitor cell with graphene electrodes and acidic electrolyte (sulfuric acid and poly vinyl alcohol) [43]. This functionalization, promoted by the availability of free protons and hydroxyl groups in the electrolyte, led to an increased amount of C-OH and COOH functionalization on the graphene, which in turn, among others, greatly improved the wettability of the electrodes to the electrolyte and led to a marked enhancement of the double-layer capacitance.…”
Section: Surface Conditioning Mechanismsupporting
confidence: 76%
“…CV was hence used to investigate the electrochemical behavior of EG and SiC on silicon films in 0.1 M aqueous NaCl electrolyte at potential limits of 0.8-0.0 V vs Ag/AgCl electrode in a three-electrode system, at a scan rate of 100 mV s −1 (figure 2(a)). From the CV curves it is observed that the EG possesses a substantially enhanced (about 1.8 times) capacitive behavior compared to the SiC film on highly doped silicon (figure 2(a)) [43,44]. The CV curve of SiC shows redox peaks (oxidation peak at 0.28 V and reduction peak at 0.18 V), possibly due to the presence of metallic impurities.…”
Section: Resultsmentioning
confidence: 97%
“…Finally, it should be noted that defective graphenic material is generally superior to low-defect graphene as an electrode for supercapacitors, being more chemically active and providing a higher amount of charge storage sites [8,41,44]. However, a highly defective graphenic layer is not efficient in combination with MoS 2 (figures S2 and S7), because of the lack of a highly conductive medium.…”
Section: Resultsmentioning
confidence: 99%
“…Charge storage in electrochemical supercapacitors relies principally on the presence of an electrical double layer at the electrode/electrolyte interface [4,7]. Redox reactions or pseudocapacitance can also contribute to charge storage [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The epitaxially grown 3C-SiC on silicon can be graphitized selectively at the wafer scale utilizing common silicon processing methods such as photolithography, etching, spin coating, sputtering, thin-film formation, and integrated circuitry. The graphene is grown epitaxially on a 3C-SiC on silicon pseudosubstrate using a catalytic alloy of nickel and copper to grow epitaxial graphene on silicon at a relatively low temperature (∼1100 °C). , Uniform, highly conductive graphene can be obtained selectively at the wafer-scale, with sufficient adhesion to its substrate . The use of a highly doped silicon substrate underneath the SiC film leads to strong carrier inversion at the SiC/Si interface, which becomes conductive .…”
Section: Noninvasive Neural Interfacesmentioning
confidence: 99%